Influence of rare earth doping on the structural and electro-magnetic properties of SmFeAsO0.7F0.3 iron pnictide1. Issue 8 (28th August 2015) - Anooja, J. B.; Aswathy, P. M.; Varghese, Neson; Chandrakanth, C. K.; Devendra Kumar, N.; Sundaresan, A.; Syamaprasad, U.
<x xml:space="preserve">Abstract</x> The effect of Gd and Ce doping on the structural and transport properties of the (Sm, RE)FeAsO0.7F0.3 superconductor.